A redistricting problem applied to meter reading in power distribution networks - Assis, Laura Silva De; Franca, Paulo Morelato [UNESP]; Usberti, Fábio Luiz (Elsevier, 2014)
The capacitated redistricting problem (CRP) has the objective to redefine, under a given criterion, an initial set of districts of an urban area represented by a geographic network. Each node in the network has different types of demands and each district has a limited capacity. Real-world applications consider more than one criteria in the design of the districts, leading to a multicriteria CRP (MCRP). Examples are found in political districting, sales design, street sweeping, garbage collection and mail delivery. This work addresses the MCRP applied to power meter reading and two criteria are considered: compactness and homogeneity of districts. The proposed solution framework is based on a greedy randomized adaptive search procedure and multicriteria scalarization techniques to approximate the Pareto frontier. The computational experiments show the effectiveness of the method for a set of randomly generated networks and for a real-world network extracted from the city of São Paulo. © 2013 Elsevier Ltd.
Keywords: Capacitated clustering; GRASP; Multicriteria optimization; Redistricting problems; Computational experiment; Greedy randomized adaptive search procedure; Power distribution network; Real-world networks; Operations research; Computer science